2019
DOI: 10.1038/s41393-018-0233-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations between leisure time physical activity and cardiovascular risk factors among older adults with long-term spinal cord injury

Abstract: Study Design This is a cross-sectional study. Objectives To describe the association between cardiovascular risk factors (body mass index (BMI), waist circumference (WC), blood pressure, blood glucose and lipids) and leisure time physical activity (LTPA) in older adults with long-term spinal cord injury (SCI). Setting Community settings, southern Sweden. Methods Data from the baseline data collection of the Swedish Aging with Spinal Cord Injury Study (SASCIS) (n = 123, 71% men, injury levels C1-L5, American Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…While all can benefit from travel participation, people with SCI or mobility challenges (including the elderly) particularly benefit from travel and tourism as a mentally and physically healthy pursuit [6]. This is largely because it reduces their perception of isolation or boredom, allowing them to enjoy public resources (i.e., recreational, educational, and cultural) and enhance their social skills and relationships [56,57]. Recent research has also indicated that travel is a key indicator of successful rehabilitation for PwSCI [58], as it may further improve their sense of competence and autonomy in solving issues and maintaining coping strategies when managing obstacles in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…While all can benefit from travel participation, people with SCI or mobility challenges (including the elderly) particularly benefit from travel and tourism as a mentally and physically healthy pursuit [6]. This is largely because it reduces their perception of isolation or boredom, allowing them to enjoy public resources (i.e., recreational, educational, and cultural) and enhance their social skills and relationships [56,57]. Recent research has also indicated that travel is a key indicator of successful rehabilitation for PwSCI [58], as it may further improve their sense of competence and autonomy in solving issues and maintaining coping strategies when managing obstacles in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported physical activity is problematic in the SCI population and the proposed final outcome indicator will not be immune to this limitation. 47 , 48 Although physical exercise recall can be problematic, it was shown to be feasible when using recall periods of 7 days 49 or less. 50 Knowledge retention regarding the guidelines for physical exercise in the SCI population were noted as potentially problematic during the Plan-Do-Study-Act cycles.…”
Section: Discussionmentioning
confidence: 99%
“…In persons with SCI, it has been indicated that increasing BMI/ weight, may decrease mobility and participation [4]. Further, associations between BMI and leisure time physical activity have been identi ed [5]. In summary, the evidence suggests a bi-directional relationship between various measures of nutritional status and activity level.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, the impact of the motor system and hence reduced opportunity for physical activity affect energy expenditure. [4,5]. Therefore, the sequela of disease mechanisms after SCI predisposes to changes in body composition, possibly affecting weight [6,7].…”
Section: Introductionmentioning
confidence: 99%